Risk of breast cancer associated with estrogen DNA adduct biomarker - Reding, Kerryn W. (Cancer Epidemiol Biomarkers Prev, 2020)
BACKGROUND: It is biologically plausible that genotoxic estrogens, namely estrogen DNA adducts (EDA), have a role in breast cancer development. Support comes from three prior studies which reported elevated concentrations of EDA relative to estrogen metabolites and conjugates (EDA:EMC) in women with breast cancer relative to control women. METHODS: In postmenopausal women in the Women’s Health Initiative (WHI), EDA:EMC in 191 controls was compared to findings in 194 pre-diagnosis urine samples from breast cancer cases. EDA:EMC determinations were by mass spectrometry as previously described, and logistic regression was employed to estimate the odds ratios (OR). RESULTS: The EDA:EMC did not differ in breast cancer cases compared to controls overall (0.93 [95% CI: 0.71–1.23]), with a mean (SD) of 2.3 (0.8) and 2.4 (1.1) in cases and controls, respectively. Similarly, the ratio did not differ when examined by estrogen receptor or recency of biospecimen collection prior to breast cancer. CONCLUSION: Despite the demonstrated genotoxic properties of certain catechol estrogens resulting in estrogen DNA adducts, this analysis did not provide evidence for an increased breast cancer risk in relation to an elevated EDA:EMC. IMPACT: This analysis conducted prospectively within post-menopausal women in the WHI study suggests that a strong association between EDA:EMC with breast cancer could be ruled out, as this study was powered to detect an OR of 2.2 or greater.